Amor Tellus? For a Material Culture of Care - Hyvönen, Ari-Elmeri (HannahArendt.net, 2022)
This article addresses the politics of ecological reconstruction in the Anthropocene by drawing from the thought of Hannah Arendt. The article particularly elaborates a notion of ‘material culture of care’ as a modality of mediating human interactions with non-human nature. Expanding on commentaries on the Arendtian ‘care for the world’, I read Arendt’s two essays on culture from the perspective of human/nature relationship. I suggest her commentary on the Roman notion of colere, cultivating nature, can offer us a notion of care that is embedded in the material interdependencies in the ‘web of life’. The essay also analyzes the modern concept of nature as an impediment for exercising such care, and discusses practices of tending and cultivating nature in the context of the city.